IDENTIFIKASI KADAR KATEKIN PADA GAMBIR (Uncaria Gambier Roxb) - Marlinda Marlinda (Universitas Teuku Umar, 2018)
This study aimed to identify levels of catechins in gambier. The sample used is Gambir taken in the market with differences in terms of color, shape and packaging. Solid Gambir is mashed and added with water until it becomes a paste and then filtered to produce pure gambier extract. Furthermore, it was deposited and dried then crushed and sieved with a size of 60 mesh. Samples were dissolved with ethyl acetate and ethanol in a ratio of 1:10 and then dried and tested for catechin content, tannin content, water solubility and ash content. The results showed that catechin levels in G1 samples were 50.81%, G2 samples were 40.60%, and G3 samples were 30.70% while tannin levels in G1 samples were 11.50, G2 samples were 17.21 and samples G3 of 23.51. The result of the research concluded that there were differences in the amount of catechins in the three study samples. The best catechin levels were found in the G1 sample as much as 50.81%, then the G2 sample as much as 40.60%, and the G3 sample as much as 30.70%. While the tannin content has an inverse amount of concentration than concentrates. The more the amount of katekin in gambier the lower the amount of tannin.